Applying blockchain in the modern supply chain management: Its implication on open innovation - Margareta Teodorescu; Elena Korchagina (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Over the past decade, the blockchain technology has been actively embraced by an increasing number of companies. Blockchain has proven its effectiveness not only in the financial sector, but also in logistics and supply chain management, and has received extensive coverage in the scientific literature. At the same time, the implementation of blockchain in logistics and supply chain management (SCM) is technically difficult and requires significant financial costs. In this regard, its distribution in countries across the world is uneven. In this study, we compare the implementation of blockchain in countries with developed (Germany) and emerging (Russia) economies. Thus, our study provides new findings and information on the similarities and differences in blockchain implementation strategies in countries with developed and emerging economies. This comparative analysis reveals country peculiarities and different approaches regarding the application of blockchain technologies. The research methodology is based on the case study method. Three economic sectors are selected for the cross-country comparative analysis: the energy, food, and pharmaceutical industries. The analysis is focused on the use of blockchain along all three parts of the supply chain: upstream, production and downstream. Using theory building through case studies, our research results reveal many similarities in blockchain implementation in Germany and Russia. They show that blockchain is actively used in all three analyzed sectors by companies in both countries. Moreover, the technology proves its effectiveness in both upstream and downstream parts of the supply chain. In both Germany and Russia, blockchain is mainly used by large businesses due to its high costs. However, there are some differences regarding the implementation process of the technology in both countries. Firstly, the state support is required for some Russian blockchain projects. Secondly, none of the Russian companies has the necessary "full range" of blockchain competencies, so all Russian projects are carried out in collaboration with other parties, primarily IT partners. Thirdly, most of the Russian blockchain projects are still local in nature and relate to the use of technology in the relationship between the specific supplier and corresponding consumers.
Keywords: 650; and pharmaceutical industries; blockchain; case study research; cross-country comparative analysis; developed and emerging economies; energy; food; logistics; supply chain management